2021
DOI: 10.3390/genes12121931
|View full text |Cite
|
Sign up to set email alerts
|

MiR-138-5p Suppresses Cell Growth and Migration in Melanoma by Targeting Telomerase Reverse Transcriptase

Abstract: Recent evidence suggests the existence of a miRNA regulatory network involving human telomerase reverse transcriptase gene (hTERT), with miR-138-5p playing a central role in many types of cancers. However, little is known about the regulation of hTERT expression by microRNA (miRNAs) in melanocytic tumors. Here, we investigated the effects of miR-138-5p in hTERT regulation in melanoma cells lines. In vitro studies demonstrated higher miR-138-5p and lower hTERT messenger RNA (mRNA) expression in human epidermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Furthermore, previous studies demonstrated that miR-138-5p could inhibit the progression of cancers by suppressing the proliferation, growth, and migration of cancer cells, indicating that miR-138-5p may be a cancer-related miRNA. [21][22][23] Another study showed that circ_101238/miR-138-5p/CDK6 signaling axis could inhibit cell proliferation while promoting apoptosis of keloid fibroblasts. 24 Therefore, miR-138-5p may play a pivotal role in therapeutics for tumorous and fibrotic diseases, which still needs further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies demonstrated that miR-138-5p could inhibit the progression of cancers by suppressing the proliferation, growth, and migration of cancer cells, indicating that miR-138-5p may be a cancer-related miRNA. [21][22][23] Another study showed that circ_101238/miR-138-5p/CDK6 signaling axis could inhibit cell proliferation while promoting apoptosis of keloid fibroblasts. 24 Therefore, miR-138-5p may play a pivotal role in therapeutics for tumorous and fibrotic diseases, which still needs further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…This result was in accordance with a previous study that showed a slowdown in wound healing by TAM in MCF-7 cells in a dose-dependent manner 81 . Moreover, it was previously reported that hTERT increases cell migration and its regulation with miR-138-5p suppresses cell growth and migration 82 84 .…”
Section: Discussionmentioning
confidence: 95%
“…The reaction system was then subjected to a polymerase chain reaction PCR. Based on previous research, 24 to detect the levels of miR-138-5p, a TaqMan miRNA assay kit was used to detect (Applied Biosystems, Foster City, CA, USA). Using the 2 −∆∆ Ct technique.…”
Section: Methodsmentioning
confidence: 99%